A qualitative study of perceptions of control over potential causes of death and the sources of information that inform perceptions of risk. Issue 1 (31st December 2022) - Brown, Richard; Sillence, Elizabeth; Pepper, Gillian
ABSTRACT : Background: Investigating perceptions of control over mortality risk may be fundamental to understanding health behaviours and tackling socioeconomic gradients in health. Few studies have explored perceptions of control over different causes of death and there is a lack of qualitative risk research. Our aim was to examine participants' perceptions of control over potential causes of death and the sources that inform perceptions of risk. Method: We conducted semi-structured interviews with 24 participants (14 female and 10 male) and conducted a template analysis to analyse the transcripts. Findings: We identified six themes to represent participants' perceptions of control over potential mortality risks and the sources that inform these perceptions: Health-Related Mortality Risks, External Causes of Risk, Finding Balance, Family Medical History, Online Sources of Risk and Health-Related Information, and Health Misinformation . Dying from heart disease was broadly reported as being a controllable risk, whereas cancer was mostly discussed as uncontrollable. Gender-specific cancers were perceived as posing a significant risk to life, however controlling this risk was discussed in terms of screening and treatment, not prevention. Family medical history was discussed as an informative source for longevity predictions, but less so for specific causes of death. Most risk information is retrieved from 'Dr Google', though trusted sources, such as NHS websites, are used for validation. Health misinformation online was seen as a problem experienced by other people, rather than the individual. Conclusions: Causal pathways between behaviours and specific cancers may not be obvious to individuals. Messages emphasising the broader links between diet, alcohol and general cancer risk may highlight the controllability of cancer risk through improved health behaviours. Furthermore, given the rise in health misinformation, and the belief that it is other people not ourselves that are typically susceptible to believing misinformation online, further attempts are needed to combat this growing 'infodemic'.